Komitmen Organisasi Dan Keterlibatan Pegawai Terhadap Perubahan Organisasi Melalui Voice Behaviour - Berhitu, Victor Arthur; Zacharias, Tehubijuluw; Ohoiwutun, St.K (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to analyze the effect of organizational commitment and employee involvement on organizational change through voice behavior. This study uses a descriptive-quantitative approach with a causal correlation type. The research was conducted at BKPSDM South Buru Regency. This research was conducted for 2 (two) months. The population used in this study were all 49 BKPSD employees. The method of determining the sample is full sampling. Data were analyzed using path analysis. The results of the study concluded that (1) organizational commitment has a positive and significant effect on employee voice behavior, (2) employee engagement has a positive and significant effect on employee voice behavior, (3) voice behavior has a positive and significant effect on organizational change, (4) organizational commitment does not affect organizational change, (5) employee engagement has no effect on organizational change, (6) organizational commitment has a positive and significant effect on organizational change through employee voice behavior, (7) employee engagement has a positive and significant effect on organizational change through employee voice behavior .